Effect of targeted movement interventions on pain and quality of life in children with dyskinetic cerebral palsy: a pilot single subject research design to test feasibility of parent-reported assessments - Smith, Nadine; Garbellini, Simon; Bear, Natasha; Thornton, Ashleigh; Watts, Peta; Gibson, Noula (Disability and rehabilitation, 2023)
To determine the feasibility of using parent-reported outcome measures of the Paediatric Pain Profile (PPP), Sleep Disturbance Scale for Children (SDSC) and Care and Comfort Hypertonicity Questionnaire (CCHQ) as repeated outcome measures of change at weekly intervals for children with dyskinetic cerebral palsy (CP). The secondary aim was to explore the efficacy of individualised movement intervention. In this pilot feasibility study a single subject research design was utilised. Three children with dyskinetic CP, completed 5 weeks of parent-reported baseline assessments, 8 weekly sessions of intervention and 5 weeks of follow up. All children completed 18 weeks of the study, with no missing data. There was evidence of parent-reported improvements in their child's pain and care and comfort between the baseline and intervention phases. The PPP, SDSC and CCHQ were feasible to assess pain, sleep and comfort before and after an intervention in children with dyskinetic CP. There is preliminary evidence that individualised movement intervention as little as once a week may help improve pain, sleep and improve ease of care and comfort. IMPLICATIONS FOR REHABILITATIONThe Paediatric Pain Profile is feasible to identify and monitor pain, as frequently as weekly, in children with dyskinetic cerebral palsy (CP).There is preliminary evidence that movement can decrease pain in children with dyskinetic CP.Assessments and treatment in this group may be interrupted due to their complex health issues which may be a limitation when collecting repeated measures.